Evaluasi hidrolis distribusi air minum di Samanea Hill, Kecamatan Parung Panjang, Kabupaten Bogor - Kusaeri, Muhammad Husni; Sururi, Mohamad Rangga (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
The construction of drinking water pipe for SPAM services at the Samanea Hill residence, Parung Panjang District, Bogor Regency, required 34.53 liters/second, with a water leakage rate of 21.18 percent and a Qmax factor of 1.2. This condition experiences problems regarding the flow of drinking water which does not comply with the design criteria which affects the distribution of pressure, velocity and headloss in the Samanea Hill. Hydraulic evaluation of the water supply of the Samanea Hill must be carried out to optimize the existing supply system. The method used to start a network distribution is to use EPANET 2.0 software on the network. The hydraulic evaluation results show that several pipe points have a flow rate < 0.3 m/sec. In addition, simulation results also show that the headloss of several nodes exceeds 10m/km. This condition is one of the reasons for a lack of drinking water flow in the Samana Hill distribution system, so improvements must be made by changing the pipe diameter to several points of the simulation results. Therefore, it is necessary to adjust the pipe diameter and equalize the velocity and headloss in the simulation results to achieve optimal conditions for drinking water distribution.